Characteristics and yield of basic seeds of native potato (Solanum goniocalyx) obtained in temporary immersion bioreactor under greenhouse conditions - Marmolejo Gutarra, Doris; Corpus Chagua, Christopher P. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The characteristics and yield of basic seeds of two native Peruvian potato varieties "Peruanita" and "Amarilla Tumbay" (Solanum goniocalyx), obtained in temporary immersion bioreactors under greenhouse conditions, were evaluated in order to obtain quality seeds in a continuous and sustainable way to guarantee farmers' production and to meet national demand. For this purpose, microtubers and cuttings obtained by temporary immersion bioreactors (TIB) were cultivated in an area of 240 m2 at 3.201 masl, a completely randomized block design was applied with a bifactorial arrangement (varieties x propagules) of 4 treatments and 3 repetitions. The variables evaluated were: survival (SP) and plant height (AP) at 30 days, number of tubers per plant (NT), tuber diameter (DT), tuber weight (PT), tuber size (TT), tuber skin color (CP) and yield in kg per 14.05 m2 (R). Tubers produced from the microtubers stood out from the cuttings in yield for basic seed, presenting an R=26.89 ± 0,483 kg.14.05 m-2, PT= 0,12 ±0,0036 kg and a TD= 22.59 ±0,451 mm; being the variety "Peruanita" the most optimal in number and weight of tubers per plant for basic seed. The basic seed coming from microtubers was obtained in 5 months, being an alternative to guarantee a constant production, allowing to take care of the demand of farmers and to lower the costs of production.